Distributions and phylogeographic data of rheophilic freshwater fishes provide evidences on the geographic extension of a central-brazilian amazonian palaeoplateau in the area of the present day Pantanal Wetland - Ribeiro, Alexandre C.; Jacob, Rodrigo M.; Silva, Ronnayana R. S. R.; Lima, Flavio C. T.; Ferreira, Daniela C.; Ferreira, Katiane M.; Mariguela, Tatiane C. [UNESP]; Pereira, Luiz H. G. [UNESP]; Oliveira, Claudio [UNESP] (Sociedade Brasileira de Ictiologia, 2013)
A análise do padrão de distribuição apresentado por exemplos de peixes de água doce neotropicais restritos à habitats reofílicos de cabeceira: o anostomídeo Leporinus octomaculatus, os caracídeos Jubiaba acanthogaster, Oligosarcus perdido, Moenkhausia cosmops, Knodus chapadae, Planaltina sp., o loricariídeo Hypostomus cochliodon e o auquenipterídeo Centromochlus sp. fornecem evidências de uma história compartilhada relativamente recente entre as terras altas do alto rio Paraguai e bacias de terras altas vizinhas. Restritas às cabeceiras das áreas altas nas bacias do alto rio Paraguai e bacias vizinhas, estas espécies fornecem evidências biológicas da pretérita extensão do Planalto Central Brasileiro anteriormente a origem tectônica da planície alagável do Pantanal. Disjunções ocorreram devido a barreira ecológica para estes taxons reofílicos representada pela subsidência tectônica associada à origem do Pantanal. A análise molecular de Jupiaba acanthogaster revelou que amostras da bacia do alto rio Xingu consistem no grupo-irmão de um clado mais inclusivo que inclui amostras do alto rio Arinos (alto rio Tapajós) mais o alto rio Paraguai, suportando a suposição de que a origem do alto rio Paraguai causou vicariância entre esta bacia e o alto rio Tapajós no último evento vicariante na história evolutiva do grupo.

The analysis of the distribution patterns presented by examples of freshwater fishes restricted to headwater habitat: the anostomid Leporinus octomaculatus, the characins Jubiaba acanthogaster, Oligosarcus perdido, Moenkhausia cosmops, Knodus chapadae, Planaltina sp., the loricariid Hypostomus cochliodon, and the auchenipterid Centromochlus sp. provided evidences of a relatively recent shared history between the highlands of the upper rio Paraguay and adjoining upland drainage basins. Restricted to headwater of the uplands in the upper rio Paraguay and adjoining basins, these species provide biological evidence of the former extension of the central Brazilian plateau before the origin of the Pantanal Wetland. Disjunction took place due to an ecological barrier to these rheophilic taxa represented tectonic subsidence related to the origin of the Pantanal Wetland. Molecular analysis of Jubiaba acanthogaster revealed that the sample from the upper rio Xingu basin are the sister-group of a clade that includes samples from the upper rio Arinos (upper rio Tapajós) plus the upper rio Paraguay basin, supporting the assumption that the origin of the upper rio Paraguay basin causing vicariance between this basin and the upper rio Tapajós is the least vicariant event in the evolutionary history of the group.
Keywords: Brazil; Brazilian highlands; Historical biogeography; Paleodrainage; Tectonic evolution